Bullerengue in Urabá, a complex sociocultural manifestation An inter dimensional perspective (Encuentros, 2022)
This text presents bullerengue as a socio-cultural practice that is difficult to fragment without falling into its simplification and sacrificing its full understanding. It means an attempt to gather what has been commonly separated in the existing studies on this manifestation (party, music and dance), but without losing sight of its junctures, through two dimensions of analysis artistic-cultural and socio-spatial. The text refers to a recent research experience in Urabá (region located in the department of Antioquia, north-western Colombia), a project called Bullerengue in Urabá, an approach to a complex sociocultural manifestation (2018-2019), which from an interdisciplinary focus integrates ethnomusicology, dance studies, socio-spatial studies and ethnography.